Bacteriophage Tuc2009 Encodes a Tail-Associated Cell Wall-Degrading Activity - Kenny, John G. (American Society for Microbiology, 2004)
Tuc2009 is a P335-type member of the tailed-phage supergroup Siphoviridae and was originally identified as a resident prophage of the gram-positive bacterium Lactococcus lactis UC509. A Tuc2009 gene designated tal(2009) which is located within the morphogenic module was shown to specify a lytic activity within the 3′ portion of its coding region. Comparative sequence analysis indicated that the cell wall-degrading part of Tal(2009) is a member of the M37 protein family and that Tal(2009) lacks a cell-binding domain, a finding supported by binding studies. Tal(2009) appears to undergo self-mediated posttranslational processing in both L. lactis and Escherichia coli. Antibodies directed against a purified C-terminal portion of Tal(2009) were used for immunoelectron microscopy, which showed that Tal(2009) is located at the tail tip of Tuc2009. Antibody neutralization studies demonstrated that Tal(2009)-directed antibodies inhibited the ability of phage to mediate host lysis by more than 100-fold. These data indicate that tal(2009) encodes a tail-associated lysin involved in localized cell wall degradation, thus allowing the Tuc2009 DNA injection machinery access to the membrane of its bacterial host.